Income inequality shift paradigm: From economic approach to sharing responsibilities - Claudia-Andreea Toma; Cristina Boboc; Valentina Vasile; Simona Ioana Ghiță (Amfiteatru Economic Journal, 2021)
This paper investigates the dynamics associated with inequality in EU member states. The variation of the Gini coefficient is analyzed from different perspectives: economic growth, certain macroeconomic variables, socio-demographic environment and historical, political and cultural environment. The use of the panel data regression model allows country specific effects control, the results showing that in the context of European convergence, the historical, political, cultural and socio-demographic factors have the greatest impact in terms of income distribution. Starting from the complex analysis of the evolution of inequalities in the last half century and from the experts' opinions regarding the relationship between the last two crises (from 2008 and the current pandemic), we notice important changes, there is a paradigm shift. The paper proposes a new approach to the economic growth paradigm, based on reversing the dynamics of income inequality in the 21st century and outlines our own vision on support policies to mitigate rising inequalities, in the context of designing a robust resilience strategy and sustainable post-pandemic development.
Keywords: O15; C23; J30; 330; Income inequality; Gini coefficient; Panel data regression